How Zakat Moderating the Influence of Human Development Index, Labor, Gross Regional Domestic Product on Poverty in Central Java? - Novitasari, Halla; Bahjatulloh, Qi Mangku; Wartoyo, Wartoyo (UIN Siber Syekh Nurjati Cirebon, 2023)
Abstract The purpose of this study was to find out how strong the influence of the Human Development Index (IPM), labor, and Gross Regional Domestic Product (GDP) on poverty in Central Java in 2017-2021 with the distribution of zakat as a moderating variable. This research is quantitative with secondary data taken from the National Baznas of Central Java Province and the BPS website. The data used is panel data, which is a combination of time series data from 2017-2021 and cross section data of 35 regencies or cities. The analysis tool uses eViews 9.0 with a random effect model selected regression analysis. The results showed that the HDI variable had a significant negative effect on poverty, while labor and GRDP had no effect on poverty. While zakat can moderate HDI and labor through poverty, zakat cannot moderate labor through poverty.Keywords: HDI, Labor, GRDP, Poverty, Distribution of Zakat Abstrak Tujuan penelitian ini untuk mengetahui seberapa kuat pengaruh Indeks Pembangunan Manusia (IPM) , tenaga kerja, dan Produk Domestik Regional Bruto (PDRB) terhadap kemiskinan di Jawa Tengah tahun 2017-2021 dengan distribusi zakat sebagai variabel moderating. Penelitian ini ialah kuantitatif dengan data sekunder yang diambil dari baznas Provinsi Jawa Tengah dan website BPS. Data yang digunakan data panel yaitu gabungan data time series dari 2017-2021 dan data cross section sebanyak 35 kabupaten atau kota. Alat analisis menggunakan eviews 9.0 dengan analisis regresi terpilih random effect model. Hasil penelitian menunjukkan variabel IPM berpengaruh negatif signifikan terhadap kemiskinan, sedangkan tenaga kerja dan PDRB tidak berpengaruh terhadap kemiskinan. Sementara zakat dapat memoderasi IPM dan tenaga kerja melalui kemiskinan, sedangkan zakat tidak dapat memoderasi tenaga kerja melalui kemiskinan.Kata kunci: IPM, Tenaga Kerja, PDRB, Kemiskinan, Distribusi Zakat